Characterization and bioactivities of a novel polysaccharide obtained from Gracilariopsis lemaneiformis - SHI,CHEN-SHAN (2017)
ABSTRACT Gracilariopsis lemaneiformis is a type of red alga that contains seaweed polysaccharide agar. In this study, a novel non-agar seaweed polysaccharide fraction named GCP (short of crude polysaccharide obtained from Gracilariopsis lemaneiformis) was isolated from Gracilariopsis lemaneiformis. Structural analysis showed that GCP shows triple helical chain conformation when dissolved in water and has many branches and long side chains. Also, 1→3 linkage is the major linkage and the sugar structures are galactopyranose configurations linked by β-type glycosidic linkages. Two macromolecular substance fractions (GCP-1 and GCP-2) were purified by DEAE Sepharose Fast Flow column chromatography. Moreover, a splenocyte damage assay and splenocyte proliferation assay were used to analyse the bioactivities of GCP, GCP-1 and GCP-2. It was demonstrated that polysaccharides could protect splenocyte damaged by H2O2; GCP-2 shows a greatest protection rate, that is, 92.8%, which significantly enhanced the splenocyte proliferation, and GCP showed the highest proliferation rate, 9.30%. The results suggested that this type of novel non-agar polysaccharide displayed remarkable antioxidant and immunomodulatory activities and early alkali treatment could decrease the activities. It may represent a potential material for health food and clinical medicines.